Evaluasi Transparansi Layanan Keuangan Dayah Jami’ah Al-Aziziyah Berbasis Fuzzy Servqual dan Importance Performance Analysis (IPA) - Rizki Ananda (Yayasan Madinah Al-Aziziyah, 2025)
Financial transparency is a critical aspect of building trust between educational institutions and stakeholders, particularly parents of students (wali santri). This study aims to evaluate the transparency and quality of financial services at Dayah Jami’ah Al-Aziziyah using an integrated Fuzzy Service Quality (Fuzzy Servqual) and Importance Performance Analysis (IPA) approach. A quantitative descriptive-evaluative method was employed, with data collected through questionnaires distributed to 85 respondents selected using the Slovin formula from a total population of 500 wali santri. Each item was assessed on a Likert scale of 1–5 for both perceived performance (kenyataan) and expected importance (harapan), and subsequently converted into Triangular Fuzzy Numbers (TFN) to accommodate subjectivity and uncertainty in responses. Defuzzification results reveal that several service attributes exhibit negative GAP values, indicating that actual performance falls short of expectations. IPA mapping further classified the 14 items into four quadrants: Quadrant I (Priority) covers items 8, 9, 10, and 11 related to Responsiveness and Assurance dimensions, which require immediate improvement; Quadrant II (Maintain) covers items 2 and 4 from Tangible and Reliability dimensions that must be sustained; Quadrant III (Low Priority) covers items 6, 7, and 14 from Reliability and Empathy dimensions; and Quadrant IV (Excessive) covers items 1, 3, 5, 12, and 13 where resources may be reallocated. These findings provide strategic recommendations for improving financial service quality and transparency at Dayah Jami’ah Al-Aziziyah.